Energy balance over one athletic season - Silva, A. M.; Matias, C. N.; Santos, D. A.; Thomas, D.; Bosy-Westphal, A.; Müller, M. J.; Heymsfield, S. B.; Sardinha, L. B. (Medicine & Science in Sports & Exercise, 2017)
INTRODUCTION: Magnitude and variation in energy balance (EB) components over an athletic season are largely unknown.